FREKUENSI DAN FAKTOR RISIKO KUNJUNGAN ANTENATAL CARE: Frequency and Factor Effecting of Antenatal Care Visit - Sari Priyanti; Dian Irawati; Agustin Dwi Syalfina (LPPM - STIKES Pemkab Jombang, 2020)
Antenatal care is a program that can reduce maternal and infant mortality. Antenatal care program is able to detect complications early in pregnancy followed by health education and prevention of pregnancy complications. The standard frequency of antenatal care visits based on WHO recommendations in 2016 is 8 times. The study aims to analyze the risk factors that influence the frequency of antenatal care visits. The research used was an analytic epidemiological study with a cross sectional approach. The dependent variable was pregnant women at the puskesmas and the independent variables were age, education, occupation, family income, parity, perception, family support, husband support, knowledge. The number of samples obtained from the calculation of the simple random sampling formula is 140. After the data was collected, it was processed and then analyzed univariate, biavariate, multivariate. Statistical test results show that risk factors that influence the frequency of antenatal care visits are parity (PR = 2,453; 95% CI = 1,129-5,331; Pvalue = 0.023) and knowledge (PR = 5,114; 95% CI = 1,878-13,922; Pvalue = 0.001). Good knowledge of pregnant women about antenatal care checks then antenatal care pregnancy visits with the number of visits ? 6 times. The higher the mother's understanding of the importance of antenatal care for maternal and infant health, the better behavior to get health services for pregnancy. Health workers are expected to apply the ANC visit frequency standard in accordance with WHO 2016 standards and increase maternal knowledge about pregnancy to family planning through pregnant mother classes. Keywords : risk factor, frekuency, visits, antenatal care